Educational Assessment in the New Mexican School. An essay from Upper Secondary Education - Jiménez Moreno, José Alfonso (2025)
This paper addresses the problem of the conceptualization of educational evaluation from the New Mexican School (NEM) as an educational ideology recently implemented in Mexico. NEM is an educational perspective that rejects the notion of educational evaluation consolidated in previous Mexican governments and policies, seeking to establish an evaluation notion closer to the formative evaluation and to distance itself from its summative uses. In this regard, the paper presents a critique of the educational evaluation concept promoted by the NEM for Upper Secondary Education, considering for this purpose the policy documents that seek to establish the NEM within this educational level. It concludes that the concept of evaluation of the NEM is not specific enough to be able to implement it within each school, as well as in the classroom; additionally, the essay considers the possibility of developing studies with Upper Secondary Education teaching staff in order to make concrete proposals that contribute to the understanding and articulation of educational evaluation in the NEM framework.